Treasure Island - Mackinnon, Mairi; Plumbe,Scott (London Usborne, 2017)
Usborne story books retell stories that children know and love, in a way that really builds their confidence in reading for themselves, at the back of the book there are activities and talking points
English stories
Keywords: English stories